Visibility, transparency and gossip How did the religion of some (Muslims) become the public concern of others? - Amiraux, Valérie (2016)
Over the last 30 years, the publicly visible "otherness" embodied by the Muslim population in the member states of the European Union has sparked movements of transnational public discussions mainly driven by the fear of the collapse of "national cohesion." This paper engages theoretically with the idea that these debates have become an ordinary trap for European publics, France being the main illustration in the text. It is more specifically concerned with the discussions surrounding the recent ban on the wearing of the full veil in French public space, asking: what does the omnipresence of public discussions about religious otherness reveal of the national culture of citizenship? What are the epistemological and political implications of the evaluation of daily individual experiences as criminal in secular contexts? The text develops some speculative readings of the public experience arising from the visibility of Islamic religious signs and the capital attached to their visibility.
Keywords: Headscarf; Muslims; Citizenship; Gossip; Public; Visibility